2023
DOI: 10.3390/en16031396
|View full text |Cite
|
Sign up to set email alerts
|

State-of-Art Review on Chemical Indicators for Monitoring the Aging Status of Oil-Immersed Transformer Paper Insulation

Abstract: Chemical compounds dissolved in insulating oil, as indicators can excellently monitor the paper aging condition, which has attracted increasing interest in areas of transformer condition monitoring and fault diagnosis. Because of their outstanding features, such as good correlation with the degree of polymerization of cellulose paper and the aid of non-destructive online monitoring, chemical indicators have been effectively used for transformer condition assessment. In this study, a comprehensive, in-depth ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 133 publications
0
9
0
Order By: Relevance
“…The papers [11,13,34] present the characteristics of furan compounds, their application, the factors that have a significant influence on the composition of 2-FAL in transformer oil and the difficulties associated with their correlation with DP. It was also found that 5-HMF and then 2-FAL are produced in the process of solid insulation degradation, and that the concentration of 5-HMF increases with age.…”
Section: Names Of Furan Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers [11,13,34] present the characteristics of furan compounds, their application, the factors that have a significant influence on the composition of 2-FAL in transformer oil and the difficulties associated with their correlation with DP. It was also found that 5-HMF and then 2-FAL are produced in the process of solid insulation degradation, and that the concentration of 5-HMF increases with age.…”
Section: Names Of Furan Compoundsmentioning
confidence: 99%
“…Several papers have been published to explain the ageing mechanism of the paperoil insulation system of power transformers, and their health and service life have been assessed using various parameters of the insulation system. Electrical and physico-chemical tests are generally used to determine the health of the transformer [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…where ∆t n is the nth time interval in hours, and F AA n is the accelerated aging factor within ∆t n . Finally, the average hotspot temperature θ h during the monitoring time t can be computed as shown in Equation (12). This study uses COMSOL Multiphysics 5.6 software to model oil-immersed transformers under various cooling modes.…”
Section: Forced Oil Circulation Guided Cooling Modementioning
confidence: 99%
“…The lifespan of oil-immersed transformers depends on the lifespan of the insulation paper [12,13], and many researchers have made important progress in the evaluation of the lifespan of transformer insulation paper. Among them, Kuhn and Ekenstam have proposed the zero-order and first-order kinetic equations [14,15], which were the basis for the secondorder kinetic equations proposed by Emsley [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The aging rate of the paper insulation around the winding is calculated as a function of pyrolysis (heating), hydrolysis, and oxidation with the hot-spot temperature being the influential factor, by which the loss of life is estimated during a certain period of operation of the transformer [1][2][3]. Therefore, it is crucial to maintain the hot-spot temperature within the desired limits and for this reason, many strategies for hot-spot detection have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%